Stairs 2012 Proceedings of the sixth Starting AI Researchers'Symposium - Kersting, Kristiam (IOS Press, 2014)
The Sixth European Starting AI Researchers’ Symposium (STAIRS 2012) took place in conjunction with the 20th European Conference on Artificial Intelligence (ECAI 2012), the Seventh Conference on Prestigious Applications of Intelligent Systems (PAIS 2012) as well as the Sixth International Symposium on Rules (RuleML 2012) in Montpellier, France, 27-28 August 2012.